2022
DOI: 10.2196/34013
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Equity Impact of Current Digital Health Design Practices: Protocol for a Scoping Review

Abstract: Background The field of digital health has grown rapidly in part due to digital health tools’ potential to reduce health inequities. However, such potential has not always been realized. The design approaches used in digital health are one of the known aspects that have an impact on health equity. Objective The aim of our scoping review will be to understand how design approaches in digital health have an impact on health equity. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…The scoping review methodology, as outlined by Arksey and O'Malley and the Joanna Briggs Institute (JBI) [16,17], is an appropriate approach for mapping DHIs. Scoping reviews allow flexibility when exploring the diverse and heterogenous field of digital health, are appropriate when using different sources of data (eg, peer-reviewed journals, gray literature, and expert opinions), and permit inclusion and exclusion criteria to be iteratively refined as more evidence is uncovered [16][17][18][19]. Additionally, the PRISMA-ScR (Preferred Reporting Items for Systematic Reviews and Meta-Analyses Extension for Scoping Reviews) [20] will be followed to ensure adherence to methodological standards.…”
Section: Scoping Review Methodologymentioning
confidence: 99%
“…The scoping review methodology, as outlined by Arksey and O'Malley and the Joanna Briggs Institute (JBI) [16,17], is an appropriate approach for mapping DHIs. Scoping reviews allow flexibility when exploring the diverse and heterogenous field of digital health, are appropriate when using different sources of data (eg, peer-reviewed journals, gray literature, and expert opinions), and permit inclusion and exclusion criteria to be iteratively refined as more evidence is uncovered [16][17][18][19]. Additionally, the PRISMA-ScR (Preferred Reporting Items for Systematic Reviews and Meta-Analyses Extension for Scoping Reviews) [20] will be followed to ensure adherence to methodological standards.…”
Section: Scoping Review Methodologymentioning
confidence: 99%
“…Primary directions are classified as behavioral leads (solid lines), indicating that a force tends to push toward the end. Non-primary directions (dashed lines) indicate that a force does not push towards the end [60]. The above two methods reflect the perceptual feedback and transition time series effects of the elderly population under the transition of digital health services to suit the aging process, dig deep into the elements that cause the transition dilemma, and analyze the causal logic behind this.…”
Section: Methodsmentioning
confidence: 99%
“…This echoes findings from other studies such as Gonzalez et al [80], which showed that participatory design and co-design can benefit long-term engagement with mHealth tools, and Jang et al [81], who showed how participation can improve access and enrollment in digital interventions. However, as analyzed by Evans et al [82], in future work, the definitions of participatory design or co-design need to continue to be scrutinized in order to better understand and improve the impact of these design practices on equity in health.…”
Section: Principal Findingsmentioning
confidence: 99%